Teacher autonomy for improving teacher self-efficacy in multicultural classrooms: A cross-national study of professional development in multicultural education. (2021) - Choi, Soobin; Mao, Xinyi
Highlights: Professional development in multicultural education (PDME) is beneficial to teacher. Teacher self-efficacy in multicultural classrooms (TSMC) can be developed by PDME. Teacher autonomy strengthens the relationship between PDME and TSMC. Teachers need room in their classrooms for developing TSMC acquired by PDME. Abstract: With the increasing diversity in classrooms, teachers are called upon to have the efficacy of teaching students in multicultural classrooms. Professional development in multicultural education (PDME) has been implemented across the world for equipping teachers with the efficacy that meets the educational needs of diverse students. Using data from 47 countries in the Teaching and Learning International Survey 2018, this study shows that PDME helps teachers develop teacher self-efficacy in multicultural classrooms (TSMC). We further find that teacher classroom autonomy strengthens the positive relationship between PDME and TSMC. Acknowledging that diversity in schools will continue to grow, this study provides implications for teacher learning and development, multicultural education, and the school organization.